URGENSI PENDEKATAN MULTIKULTUR DALAM PENDIDIKAN - Harjali, Harjali (Cendekia: Jurnal Kependidikan Dan Kemasyarakatan, 2011)
The Indonesian people have been in the reformation and globalization era. One of the nine reform agenda is to uphold democracy. The enforcement of the democratic life means the recognition of human rights. In this regard, the recognition includes the uniqueness of the existence of Indonesias pluralist society. Therefore, the symbol of unity in diversity shows recognition to the existence of a unified pluralism of the Indonesian society. In accordance with the enforcement agenda of democratic society, there have been serious efforts to promoting the improvement of the national education system. However, the national education policy tends to generalize the Indonesian people and neglect the essence of human diversity and a pluralistic culture of Indonesia. As a matter of fact, it can not be denied that this country absolutely need for multicultural education in the broadest sense, which is the educational system that can best accommodate the diversity of society to be one of national unity.Â ÙÙÙÙ Ø§ÙÙØ¬ØªÙØ¹ Ø§ÙØ¥ÙØ¯ÙÙÙØ³Ù Ø§ÙØ¢Ù ÙÙ Ø¹ØµØ± Ø§ÙØªØ¬Ø¯ÙØ¯ ÙØ§ÙØ¹ÙÙÙØ©.ÙÙÙ Ø¨Ø±Ø§ÙØ¬ Ø§ÙØªØ¬Ø¯ÙØ¯ Ø§ÙØªØ³Ø¹Ø© ÙÙ Ø¥ÙØ§ÙØ© Ø§ÙÙÙÙ Ø§ÙØ¯ÙÙÙÙØ±Ø§Ø·ÙØ©. ÙØ¥ÙØ§ÙØ© Ø§ÙØ¯ÙÙÙÙØ±Ø§Ø·ÙØ© ØªØ¹ÙÙ Ø§ÙØ§Ø¹ØªØ±Ø§Ù Ø¨ØÙÙÙ Ø§ÙØ¥ÙØ³Ø§Ù Ø§ÙØ£Ø³Ø§Ø³ÙØ©. ÙÙØ°Ø§ Ø§ÙØ§Ø¹ØªØ±Ø§Ù ÙÙ ÙÙØ¹ Ø®Ø§Øµ ÙÙÙÙ Ø§ÙÙØ¬ØªÙØ¹ Ø§ÙØ¥ÙØ¯ÙÙÙØ³Ù Ø§ÙÙØªÙÙÙØ¹. ÙÙÙØ°Ø§ ÙØ§Ù Ø´Ø¹Ø§Ø± Ø§ÙØ¨ÙØ¯ " Ø¨ÙÙÙØ§ ØªÙÙØºØ§Ù Ø¥ÙÙØ§ " ÙØ´ÙØ± Ø¥ÙÙ ÙØ°Ø§ Ø§ÙØªØ¬ÙÙØ¹ Ø§ÙÙØªÙÙÙØ¹ Ø§ÙÙÙØÙØ¯. ÙØ¥ØµÙØ§Ø Ø§ÙÙØ¸Ø§Ù Ø§ÙØªØ±Ø¨ÙÙ Ø§ÙÙØ·ÙÙ ÙÙ Ø¨Ø±ÙØ§ÙØ¬ Ø¥ÙØ§ÙØ© Ø§ÙÙØ¬ØªÙØ¹ Ø§ÙØ¯ÙÙÙÙØ±Ø§Ø·Ù. ÙÙÙ Ø§ÙØ¹ØµØ± Ø§ÙØªØ±Ø¨ÙÙ ÙÙÙÙ Ø¥ÙÙ ØªØ³ÙÙØ© Ø§ÙÙØ¬ØªÙØ¹ Ø§ÙØ¥ÙØ¯ÙÙÙØ³Ù ÙØ§ÙÙØ§Ù ØªÙÙÙØ¹Ø§Øª Ø§ÙÙØ§Ø³ ÙØ§ÙØ«ÙØ§ÙØ© Ø§ÙØ¥ÙØ¯ÙÙÙØ³ÙØ© Ø§ÙÙØ®ØªÙÙØ©. ÙØ§ØØªØ§Ø¬ ÙØ°Ø§ Ø§ÙØ¨ÙØ¯ Ø¥ÙÙ ÙØ¸Ø§Ù Ø§ÙØªØ±Ø¨ÙØ© Ø¨ÙØ¯Ø®Ù ÙØªØ¹Ø¯ÙØ¯ Ø§ÙØ«ÙØ§ÙØ§Øª Ø¨ÙØ¹ÙØ§Ù Ø§ÙÙØ§Ø³Ø¹Ø ÙÙ Ø§ÙØªØ±Ø¨ÙØ© Ø§ÙØªÙ ØªØ¹ØªØ±Ù Ø¨ØªÙÙÙØ¹Ø§Øª Ø§ÙÙØ¬ØªÙØ¹ Ø§ÙØ¥ÙØ¯ÙÙÙØ³Ù ØªÙØÙØ¯ ÙØ·ÙÙÙ.Â Â Â